Phosphatidylinositol‐3, 4, 5‐triphosphate‐dependent Rac exchange factor 1 regulates epinephrine‐induced exocytosis of Weibel–Palade bodies. (February 2014) - van, K. W. E. M.; van, D.; Fernandez‐Borja, M.; Meijer, A. B.; Eikenboom, J.; Bierings, R.; Voorberg, J.
Summary Background Weibel–Palade bodies (WPBs) function as storage vesicles for von Willebrand factor (VWF) and a number of other bioactive compounds, including angiopoietin‐2 and insulin‐like growth factor‐binding protein 7. WPBs release their content following stimulation with agonists that increase the level of intracellular Ca2+, such as thrombin, or agonists that increase intracellular levels of cAMP, such as epinephrine. Objective Previously, we have shown that the exchange protein activated by cAMP, exchange protein activated by cAMP, and the small GTPase Rap1 are involved in cAMP‐mediated release of WPBs. In this study, we explored potential downstream effectors of Rap1 in cAMP‐mediated WPB release. Methods Studies were performed in primary human umbilical vein endothelial cells. Activation of the small GTP‐binding protein Rac1 was monitored by its ability to bind to the CRIB domain of the serine/threonine kinase P21‐activated kinase (PAK)1. Downstream effectors of Rap1 were identified with a proteomic screen using a glutathione‐S‐transferase fusion of the Ras‐binding domain of RalGDS. Functional involvement of candidate proteins in WPB release was determined by RNA interference (RNAi)‐mediated knockdown of gene expression. Results Depletion of Rac1 by RNAi prevented epinephrine‐induced VWF secretion. Also, the Rac1 inhibitor EHT1864 reduced epinephrine‐induced WPB release. We identified the phosphatidylinositol‐3, 4, 5‐triphosphate‐dependent Rac exchange factor 1 (PREX1) and the regulatory β‐subunit of phosphatidylinositol 3‐kinase (PI3K) as downstream targets of Rap1. The PI3K inhibitor LY294002 reduced epinephrine‐induced release of VWF. RNAi‐mediated downregulation of PREX1 abolished epinephrine‐induced but not thrombin‐induced release of WPBs. Conclusion Our findings show that PREX1 regulates epinephrine‐induced release of WPBs.